Shift of microRNA profile upon glioma cell migration using patient-derived spheroids and serum-free conditions - Munthe, Sune (J Neurooncol, 2017)
Glioblastoma multiforme (GBM) is the most frequent malignant primary brain tumor. A major reason for the overall median survival being only 14.6 months is migrating tumor cells left behind after surgery. Another major reason is tumor cells having a so-called cancer stem cell phenotype being therefore resistant towards traditional chemo- and radiotherapy. A group of novel molecular targets are microRNAs (miRNAs). MiRNAs are small non-coding RNAs exerting post-transcriptional regulation of gene expression. The aim of this study was to identify differentially expressed miRNAs in migrating GBM cells using serum-free stem cell conditions. We used patient-derived GBM spheroid cultures for a novel serum-free migration assay. MiRNA expression of migrating tumor cells isolated at maximum migration speed was compared with corresponding spheroids using an OpenArray Real-Time PCR System. The miRNA profiling revealed 30 miRNAs to be differentially expressed. In total 13 miRNAs were upregulated and 17 downregulated in migrating cells compared to corresponding spheroids. The three most deregulated miRNAs, miR-1227 (up-regulated), miR-32 (down-regulated) and miR-222 (down-regulated), were experimentally overexpressed. A non-significantly increased migration rate was observed after miR-1227 overexpression. A significantly reduced migration rate was observed after miR-32 and miR-222 overexpression. In conclusion a shift in microRNA profile upon glioma cell migration was identified using an assay avoiding serum-induced migration. Both the miRNA profiling and the functional validation suggested that miR-1227 may be associated with increased migration and miR-32 and miR-222 with decreased migration. These miRNAs may represent potential novel targets in migrating glioma cells.